Analisis Hubungan Kondisi Psikologis dengan Kecanduan Gadget pada Remaja Selama Masa Pandemi Covid 19 di Kota Padang - Randy Refnandes; Lili Fajria; Nelwati Nelwati (Universitas Batanghari Jambi, 2022)
The use of digital technology is a general term that includes various devices, services, and types of use. This study aims to determine the relationship between psychological conditions and gadget addiction in adolescents in Padang City. This research uses a cross sectional study design which will be conducted from April to September 2021. This research was conducted in the community. Instrument. The sample in this study used an Acidal sampling technique with a purpose sampling technique of 244 respondents. The results showed that they were female (71.3%), more than half of the respondents were in their late teens (64.4%). addicted to online games, most of the respondents experience online game addiction as much as 54.5%. the relationship between the level of anxiety with online game addiction in respondents who experience severe anxiety mostly experience online game addiction as much as 72.2%. It is hoped that the results of this study can be used as reference data or comparisons for research related to factors that influence depression in adolescents.